Analysis of stress intensity factor for a crack emanating from elliptical hole subjected to compressive stress and shear stress. (August 2022) - Huang, Jianwei; Wang, Hanbing; Zhou, Lei; Zhu, Zheming; Deng, Ze; Deng, An
Highlights: An analytical formulas of a crack emanating from an elliptical hole under compressive loads, shear loads and internal pressure were proposed. The analytical results of the SIFs were verified by using the ABAQUS code. The effects of compressive stress, crack inclination angle, shear stress, internal pressure, crack length and the shape of the elliptical hole on the SIFs were discussed. The effects of different factors on crack initiation angle and crack initiation pressure were discussed using analytical equations. Abstract: Underground caves often exist in karst areas, which will cause many difficulties in tunnel construction. The underground caves are often subjected to compressive stress, shear stress and internal pressure come from rock, faults and groundwater, respectively. The crack emanating from the cave will propagate under the effect of external forces, leading to the disaster of cave collapse and water gushing. To research the stability of crack emanating from the elliptical cave, a model of a plane containing an elliptical hole with a single crack under the compressive stress, shear stress and internal pressure was established. The theoretical solutions of stress intensity factors (SIFs) for crack tip were derived using complex variable function and conformal mapping function. The theoretical results were compared with the results of numerical simulation to verify the correctness of the theoretical solutions. The effects of crack length, ellipse shape, compressive stress, shear stress, internal pressure and crack inclination angle on SIFs were discussed. We can conclude that when the crack inclination angle is varied from 0° to 30°, the initiation pressure is small, and the cave is easily destroyed by groundwater. The flatter the elliptical hole, the easier the crack propagates. With an increasing of crack length, the value of SIFs at the crack tip increase quickly first and then increase linearly. When the crack inclination angle is 45°, the initiation angle of the crack reaches the maximum value.